2014
DOI: 10.1177/2041731414556561
|View full text |Cite
|
Sign up to set email alerts
|

The fusion of tissue spheroids attached to pre-stretched electrospun polyurethane scaffolds

Abstract: Effective cell invasion into thick electrospun biomimetic scaffolds is an unsolved problem. One possible strategy to biofabricate tissue constructs of desirable thickness and material properties without the need for cell invasion is to use thin (<2 µm) porous electrospun meshes and self-assembling (capable of tissue fusion) tissue spheroids as building blocks. Pre-stretched electrospun meshes remained taut in cell culture and were able to support tissue spheroids with minimal deformation. We hypothesize that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…This fact is in good accordance with previous published reports about attachment, spreading and fusion of tissue spheroids placed manually on electrospun matrices [21,22] . The main advantage in using 3D bioprinter for automated placing of tissue spheroids is a possibility to create regular pattern of their redistribution and, thus, to control the resulted thickness of bioprinted tissue construct.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This fact is in good accordance with previous published reports about attachment, spreading and fusion of tissue spheroids placed manually on electrospun matrices [21,22] . The main advantage in using 3D bioprinter for automated placing of tissue spheroids is a possibility to create regular pattern of their redistribution and, thus, to control the resulted thickness of bioprinted tissue construct.…”
Section: Discussionsupporting
confidence: 82%
“…Fabrication of nano-/microfibrous synthetic scaffolds by electrospinning is one of popular application of nanotechnology in tissue engineering [19,20] . It has been demonstrated that tissue spheroids can attach, spread and fuse on synthetic electrospun matrices [21,22] . Moreover, recently reported magnetic functionalization of electrospun synthetic matrices with magnetic nanoparticles [23] as well as biofabrication of tissue spheroids from cells labelled with magnetic nanoparticles [24][25][26][27] allow the development of magnetic forcesdriven biofabrication and even 3D magnetic bioprinting based on principles of magnetic levitation [28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] For the regeneration of hard tissues like bone and tooth structure, bioactive inorganic phases have been attractive through providing chemical and/or physical bone-bioactive cues to the cells involved in osteogenic processes. Inorganic nanofibers have poor mechanical stability and are not effective when used as cell supporting matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Layer-by-layer composition in this study allowed for the design of a double-layered vascular wall exhibiting patterns of smooth muscle cell and fibroblast organization (61). Interestingly, placement of stem cell-based spheroids on a pre-stretched electrospun scaffold resulted in incomplete fusion and hole formation in tissue-engineered vessels, suggesting that the scaffold may impede fusion (62). Though burst pressure as a functional parameter was not assessed in these spheroid-based studies, the results demonstrate the ability to finely control structural architecture in vascular tissue engineering and achieve small-diameter vessels (<5mm).…”
Section: Primarily Mechanically Functional Tissuesmentioning
confidence: 99%